Tinjauan Kelengkapan Diagnosis Visum Et Repertum Psikiatrik di Rumah Sakit Jiwa Daerah Sambang Lihum Tahun 2015 - Aris Antoni; Gussa Azizah; Dinar Tiara Kahayani; STIKES Husada Borneo; RSUD Banjarbaru; Alumni STIKES Husada Borneo (HB PRESS, 2015)
Visum et repertum psychiatric report or a written statement from a specialist doctor of psychiatry at the request of the investigator, a visum et repertum psychiatric intended for the suspect or the accused criminal. In Sambang Lihum Psychiatric Hospital, patient diagnosis post mortem has not been charged and written by PPDGJ III by physicians who perform the autopsy report. This resulted in poor quality of medical records because of the difficulty attendant codefication to encode diagnoses that have been set by the examining physician. The purpose of this study was to determine the completeness of a visum et repertum psychiatric diagnoses in Psychiatric Hospital Sambang Lihum. The method used is descriptive with a population and sample were the medical records of visum et repertum psychiatric patients. Based on this research, a visum et repertum diagnosis of psychiatric patients are still many who are not filled in the medical record, just fill in the form visum et repertum. In the form visum et repertum diagnosis is based on 100% PPDGJ III, according to the doctor if you use a diagnosis based PPDGJ III feared the court did not understand the diagnosis. Standard operating procedures in the visum et repertum psychiatric Hospital Sambang Lihum is the sender officers came to the emergency room or outpatient. Then the officer IGD or outpatient clinic explaining the terms of a visum et repertum psychiatric to sender. If the conditions have not been complete, the sender agencies were asked to complete the terms of which required a maximum of 2 X 24 hours. For financing during the observation will be charged to the shipper or family. Factors that cause the incompleteness of medical record documents one of which is the perception of the doctor of medical records of visum et repertum psychiatric.